Stimulation of innovative behavior through the inclusive leaders and engaged workers - Mansoor, Adil; Abdul Wahab, Sazali; Jahan, Sarwat (Business: Theory and Practice, 2021)
Based on social exchange theory, this research introduced a model to understand factors that contribute towards inclusive leadership (IL) and its effect on innovative work behavior (IWB) with employee engagement (EE) as a mediator. Although the connection between IL and IWB is previously established. However, few studies have tested the potential mediation effect of EE particularly in the IT sector. Therefore, this investigation provides new insights as to how IL stimulates the innovation through the meditating impact of EE. Data collected through questionnaire were then analyzed through structural equation modeling. 116 participants have provided the data for this study. We found a positive association of IL with IWB, while the mediating effect of EE was also empirically established. This study is novel because it explained how IL can persuade their subordinates to exhibit positive behavioral outcome (i.e. IWB). Furthermore, the current study also might help the policymakers to devise effective leadership training programs so that their managers may adopt IL style and make the employees more engaged and innovative.